59.6k views
5 votes
Simplify without negative exponents x^-4/x^7

2 Answers

2 votes

I'm going to take your x^-4/x^7 and rewrite it for greater clarity:

x^(-4)

---------

x^7

If we now mult. both the numerator and the denom. of this expression by x^4, we obtain:

1

--------

x^13

which is equivalent to the given expression but without a negative exponent.


User Doc Brown
by
6.0k points
5 votes

Answer: The answer to the given expression is
(1)/(x^(11))

Explanation:

We are given an expression:
(x^(-4))/(x^7)

To simplify this, we use the laws of exponents:


  1. (x^m)/(x^n)=x^(m-n)

  2. x^(-m)=(1)/(x^m)

Simplifying the expression using law 1, we get:


\Rightarrow (x^(-4))/(x^7)=x^(-4-7)=x^(-11)

Now, using law 2, we get:


\Rightarrow x^(-11)=(1)/(x^(11))

Hence, the answer to the given expression is
(1)/(x^(11))

User Heximal
by
5.8k points